Medical school benchmarking – From tools to programmes. (February 2015) - Wilkinson, Tim J.; Hudson, Judith N.; Mccoll, Geoffrey J.; Hu, Wendy C. Y.; Jolly, Brian C.; Schuwirth, Lambert W. T.
Abstract Background: Benchmarking among medical schools is essential, but may result in unwanted effects. Aim: To apply a conceptual framework to selected benchmarking activities of medical schools. Methods: We present an analogy between the effects of assessment on student learning and the effects of benchmarking on medical school educational activities. A framework by which benchmarking can be evaluated was developed and applied to key current benchmarking activities in Australia and New Zealand. Results: The analogy generated a conceptual framework that tested five questions to be considered in relation to benchmarking: what is the purpose? what are the attributes of value? what are the best tools to assess the attributes of value? what happens to the results? and, what is the likely "institutional impact" of the results? If the activities were compared against a blueprint of desirable medical graduate outcomes, notable omissions would emerge. Conclusion: Medical schools should benchmark their performance on a range of educational activities to ensure quality improvement and to assure stakeholders that standards are being met. Although benchmarking potentially has positive benefits, it could also result in perverse incentives with unforeseen and detrimental effects on learning if it is undertaken using only a few selected assessment tools.